2010
DOI: 10.1021/jp105379x
|View full text |Cite
|
Sign up to set email alerts
|

Large-Cage Occupancies of Hydrogen in Binary Clathrate Hydrates Dependent on Pressures and Guest Concentrations

Abstract: Balancing the formation and storage pressure with the storage capacity is one of the most significant steps toward developing H 2 storage in hydrates. The large-cage occupancies of hydrogen molecules in tetrahydrofuran (THF), acetone, cyclohexanone (CHONE), and methylcyclohexane (MCH) hydrates were investigated by Raman spectroscopy, volumetric gas release measurement, and X-ray diffraction analysis in a pressure region below the equilibrium pressure of pure H 2 hydrates at 255 ( 2 K. The results from the meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 32 publications
(115 reference statements)
3
47
0
Order By: Relevance
“…17 Recent experimental results support the idea that the hydrogen content of promoted clathrates may indeed be tunable, with a reported hydrogen content of around 3.5 wt% in THF/acetone H 2 -H 2 O clathrates. 18,19 However, this number does not yet meet the DOE target.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recent experimental results support the idea that the hydrogen content of promoted clathrates may indeed be tunable, with a reported hydrogen content of around 3.5 wt% in THF/acetone H 2 -H 2 O clathrates. 18,19 However, this number does not yet meet the DOE target.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, hydrogen has received a great deal of attention in the hydrate community owing to its high potential for use in energy‐related and many other issues 7. 8 Numerous studies concerning hydrogen storage using clathrate hydrates have been reported with much efforts aimed at increasing storage capacity, introducing unusual tuning effects by changes in concentration and pressure 911. Another interesting observation about hydrogen is that atomic hydrogen radicals can be captured stably in the water cages of clathrate hydrates 2.…”
Section: Introductionmentioning
confidence: 99%
“…With a further increase in pressure, Raman peaks of triple-and quadruple-H 2 clusters were detected at ∼550 and ∼700 bar, respectively. 19 Note that conflicting arguments pertaining to experimental and simulation results have previously been raised regarding double H 2 occupancy in the 5 12 cage. 20−23 Figures 1 and 2 show Raman peaks corresponding to H 2 vibrons in hydrate samples with χ THF and χ PRD values of 0.01, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%